Themes, Reality of Society and Societal Values in Mulk Raj Anand’s Novel: Analytical Study: A Critical Analysis of Mulk Raj Anand's Novels: Depiction of Social Exploitation and Realism in Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mulk Raj Anand is extremely outstanding as an Indian novelist, recognized author, reformer, craftsmanship faultfinder, proofreader, columnist, a short story essayist and political dissident.. That is the reason he isn't just known as India's Charles dickens yet in addition considered the savior of the less wealthy, disliked, down trodden and undesirable. His writings mirror his critical social concern, distractions and the social motivation and made the peruser to be instantly mindful of the exploitation looked by the discouraged through the heart throbbing portrayal of their pathetic state. Composed with a reason both these novels censure the cutting edge free enterprise Indian society and medieval framework for the indecent and heartbreaking exploitation of poor people and underdog as there is only a genuine, genuine and unpleasant impression of the society in both the novels managing a comparative focal topic of social exploitation, the exploitation of the oppressed and the underprivileged as a result of the scourge of untouchability, poverty, hunger, child work, social governance, social set up of society, traditions, religious conviction, biases and the suffering of the Indian masses by the powers of private enterprise, industrialism and expansionism. The present investigation demonstrates the real nature of social realism in Untouchable and Coolie the epic like novels of M. K. Anand to evoke genuine emotion in the hearts of the consciententious Indians through a lovely and genuine to life depiction of the misused masses of Indian society.